A small molecule screen to identify regulators of let-7 targets. Issue 1 (December 2017) - Cinkornpumin, J.; Roos, M.; Nguyen, L.; Liu, Xiaoguang; Gaeta, X.; Lin, S.; Chan, D.; Liu, A.; Gregory, R.; Jung, M.; Chute, J.; Zhu, H.; et al.
Abstract Thelet-7 family of miRNAs has been shown to be crucial in many aspects of biology, from the regulation of developmental timing to cancer. The available methods to regulate this family of miRNAs have so far been mostly genetic and therefore not easily performed experimentally. Here, we describe a small molecule screen designed to identify regulators oflet-7 targets in human cells. In particular, we focused our efforts on the identification of small molecules that could suppresslet-7 targets, as these could serve to potentially intercede in tumors driven by loss oflet-7 activity. After screening through roughly 36, 000 compounds, we identified a class of phosphodiesterase inhibitors that suppresslet-7 targets. These compounds stimulate cAMP levels and raise maturelet-7 levels to suppresslet-7 target genes in multiple cancer cell lines such asHMGA2 andMYC . As a result, these compounds also show growth inhibitory activity on cancer cells.